THE EFFECT OF LEARNING STRATEGIES SIMULATION AND LEARNING MOTIVATION ON THE RESULTS OF ISLAMIC EDUCATION LEARNING SCHOOL STUDENTS MIDDLE FIRST STATE 4 MEDAN - Rusydi Ananda; Muhammad Rifai; Muhammad Azman (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
The research study aims to identify and describe: (1) the effect of implementing learning strategies on the learning outcomes of Islamic Religious Education students at SMP Negeri 4 Medan, (2) the influence of learning motivation on the learning outcomes of Islamic Religious Education students at SMP Negeri 4 Medan, and (3) interaction. between learning strategies and learning motivation on learning outcomes of Islamic Religious Education students of SMP Negeri 4 Medan. The population was all students of class VII SMPN 4 Medan consisting of 11 classes. The sampling technique used was cluster random sampling. The data collection instruments were questionnaires and tests. Testing for normality using Liliefors and homogeneity testing using Fisher and Bartlett. The data analysis technique is a two-way analysis of variance at α = 0.05 .The results showed: (1) there is an effect of the application of learning strategies on learning outcomes of learning outcomes in Islamic Religious Education, this is evident from the results of statistical tests which show Fcount = 4.35 > Ftable 3.96, (2) there is an effect of learning motivation on the results. learning Islamic Religious Education, this is evident from statistical testing which shows Fcount = 5.14 > Ftable 3.96, and (3) there is an interaction between learning strategies and learning motivation, this is evident from statistical testing which shows Fcount = 104.36 > Ftable 3,96.